2011
DOI: 10.4061/2011/925104
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Myocarditis with Incessant Ventricular Arrhythmias Treated Successfully with Methylprednisolone and Rat Antithymocyte Globulin

Abstract: Giant cell myocarditis is an aggressive form of this condition that is typically progressive and unresponsive to usual medical treatment. Here, we describe a 34-year-old patient presenting with incessant ventricular arrhythmias with hemodynamic compromise who required prolonged support in intensive care with an intra-aortic balloon pump (IABP). His Coronary arteries were normal and LV endomyocardial biopsy revealed myocyte necrosis with inflammatory infiltrate of lymphocytes, eosinophils, and giant cells sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Some case reports have suggested that immunosuppression may suppress arrhythmias, too, 17,19 but other reports show failures. 15,20 In our study, the response of VTs to standard amiodarone therapy was inconsistent, although the frequency of recurrences was reduced in most patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some case reports have suggested that immunosuppression may suppress arrhythmias, too, 17,19 but other reports show failures. 15,20 In our study, the response of VTs to standard amiodarone therapy was inconsistent, although the frequency of recurrences was reduced in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent multicenter study of 1-year GCM survivors found that 6 of 26 patients experienced recurrent VTs during a mean follow-up of 5.5 years, but no new VTs were observed in patients free of arrhythmias at presentation. 8 Although the above studies and several case reports [15][16][17][18][19][20] have suggested that ventricular tachyarrhythmias are both common and important in GCM, no in-depth research focusing on this subject has been published from outside our institution.…”
Section: Discussionmentioning
confidence: 99%
“…18 There are further anecdotal data from case reports of clinical improvement after immunosuppression with combinations of steroid, cyclosporine, azathioprine, muromonab-CD3, and rabbit antithymocyte globulin. 19 Heart transplantation is an effective therapy, with a 71% 5-year survival; however, GCM recurs in ≈20% to 25% of patients. 12 The decision to use an ICD and the timing of ICD placement in such cases are challenging.…”
Section: Invasive Cardiac Electrophysiology Testing Was Normal With mentioning
confidence: 99%